Analysis of Serious games against anti-bullying: playful resources to promote prosocial skills in schoolchildren - del Moral Pérez, María Esther; Villalustre Martínez, Lourdes (Revista Complutense de Educación, 2018)
The research is ascribed to Personal and Social Learning & Ethics (PSLE) that advocates for the implementation of serious games (SG) in educational contexts to promote personal and social learning from an ethical perspective. The paper analyzes the educational potential of a sample of free online anti-bullying SG (N = 10) — promoted by international educational institutions — aimed at developing prosocial skills in schoolchildren. The study adopts a qualitative methodology, focused on the content analysis, to identify the strategies they adopt on: 1) psycho-ludic and interactive aspects (typology of exposed aggressions, underlying learning theory and adopted play strategies); and, 2) the degree to which they promote different abilities (analytical, metacognitive and prosocial). Thus, it is verified that most of these games recreate simulations of verbal and physical aggression to victims and damage to their belongings, cyberbullying, threats, blackmail, humiliations, etc., inviting the player to assume roles to identify with the victim or with friends of victims. Their game mechanics help to: discriminate attitudes and negative behaviors, recognize one’s own and others’ feelings, foster empathy to connect with others, make decisions, and resolve assertive conflicts. However, they suffer from dynamics that stimulate communication (negotiating capacity, active listening and assertiveness). This work offers to primary teachers 10 attractive interactive instruments of a playful nature — simulators or role-plays — that can be integrated as didactic resources in preventive programs of the mistreatment between equals. Although they require the design of activities that activate complementary skills related to interpersonal communication, and which invite schoolchildren explicitly to reflect and critically analyze their actions, to promote respect and mutual understanding. An instrument is also presented to systematize content analysis and didactic potential of serious anti-bullying games.